(3JbhjI GdESdGe aj EKHGJ ESdGe BHGA SjO GdCfGes - (3YHO GdcQje Hf YHO GdMcje GdHNGQj GdeOfjs ((3GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg Efj deG fhjJ GdeLGhQI aj GdHdOI GdWjHI hCbeJ ajgG NeS Sfjf edGReG dNOeI GdQhVI GdefjaI hQCjJ GdRGFQjf GdPjf jLjFhf ajgG Ydi bUO JbHjd GdYJHI GdYdjI hRjGQI ef gh NGJe GdCfHjGA hSjO GdHQjI s
(3BNQgG (B:s
(3aEPG JMbbJ LejY eG PcQfG dc YdeJ Cf GdcaQ aj LejY BHGFg hCegGJg Ydjg GdSdGe ef GdGHJOGA Edi GdGfJgGA dG jecf Cf jJUh JeJ GdQSGdIs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJGQjNs